Nonferrous waste foundry sand and milling fly ash as alternative low mechanical strength materials for construction industry: effect on mortars at early ages - Vázquez Rodríguez, Francisco Javier; Valadez Ramos, Jaime Elihezer; Puente Ornelas, Rodrigo; Contreras, J. E.; Arato, A.; Rodríguez Castellanos, Edén Amaral (Bucureşti: Fundaţia "Şerban Solacolu, 2018)
An alternative solution to reduce environmental pollution using aluminum waste foundry sand (AWFS) and fly ash (FA) to produce sustainable construction materials was studied. New mortars were prepared by partially replacing ordinary Portland cement with fly ash at 5, 10 and 15 % mass. and a total replace of Ottawa sand (OS) with AWFS. The specimens were cured at 25°C with a 100% relative humidity. The mechanical behavior was evaluated by compression test at the ages of 7, 14 and 28 days. The microstructural characteristics were analyzed by scanning electron microscopy (SEM). The results indicate that the addition of milling fly ash in AWFS mortars increases the mechanical resistance, mostly at 5% mass reaching the maximum value of 10 MPa at 28 days of age. Microstructurally, it was found a porous cement matrix with some cracking caused by the reaction of portland cement with the metallic aluminum remaining in the waste sand, which is correlated to the low mechanical resistance obtained. The final mechanical characteristic makes this new product a serious candidate to be used as a sustainable building material working at low load.